Dining with wolves: Are the rewards worth the risks? - Summer N. Richman; Diana F. Tomback; Nels Grevstad; Darlene Kobobel (PLoS ONE, 2025)
Where wild populations of gray wolves (Canis lupus) occur in North America, common ravens (Corvus corax) and, in western regions, black-billed magpies (Pica hudsonia) (Family Corvidae), show up quickly at wolf kills and scavenge carcasses, often feeding near wolves. Ravens and magpies also visit wolf enclosures at gray wolf sanctuaries in Colorado, USA, and attempt to take food from wolves, but there is no information regarding how often they obtain food or are injured or killed. Working at the Colorado Wolf and Wildlife Center, Divide, Colorado, we asked whether ravens and magpies associate with gray wolves at feeding time; what proportions of ravens and magpies obtain food per enclosure; whether individual wolves react differently to the birds; and if the birds are harmed by interacting with wolves. We also examined the effects of food type, amount, and air temperature on bird numbers. We counted raven and magpie numbers in wolf enclosures and wolf and bird behaviors during daily feeding tours across 20 visits and within eight wolf enclosures per visit. Wolf reactions within each enclosure were categorized as chasing or ignoring birds or removing food. Cumulatively, across all dates and enclosures, 33% of ravens and 43% of magpies obtained food within each enclosure. Because birds were not individually marked, these percentages could be higher. Individual wolves differed in responses to ravens and magpies but most often ignored bird presence. We found no effect of food type on bird numbers but a trend in reward probability with greater food amount for ravens. There were, however, statistically significant negative relationships between daily maximum and average temperature and raven numbers, and significant positive relationships between daily minimum and average temperature and magpie numbers. We conclude that dining with wolves represented a successful foraging strategy with low risk to ravens and magpies.